(3GdeLJHi ef GdSffs - (3CHh YHO GdQMef CMeO Hf TYjH GdfSGFis; (3GdfSGFj , CMeO Hf Ydj Hf TYjH Hf Ydj Hf SfGf Hf HMQ Hf OjfGQ GdfSGFj, CHh YHO GdQMef,J (B303 (3g` s
(3ChdgG (B:s
(3Yf GdRgQi bGd QCjJ QShd Gddg Udi Gddg Ydjg hSde GdSjQai GdSaQ jDNQ UdGI GdeZQH s
(3BNQgG (B:s
(3jfJgi CKfGA HGH GdMK Ydi GdhJQ aHd Gdfhe s
(3GdfSNI HgG MhGTs
(3bWYI efgs
(3YdjgG SeGYGJ cKjQI s
(3GdMHQ dhfg HZi HGgJ ai HYV GdChQGb s
(3JHUQI GdYfhGf (B:s
(3GNJUGQs
Keywords: (3GdMOjK h GdeUWdMs